2022
DOI: 10.1136/jmg-2022-108790
|View full text |Cite
|
Sign up to set email alerts
|

Differential involvement of germline pathogenic variants in breast cancer genes between DCIS and low-grade invasive cancers

Abstract: PurposeTo investigate frequency of germline pathogenic variants (PVs) in women with ductal carcinoma in situ (DCIS) and grade 1 invasive breast cancer (G1BC).MethodsWe undertookBRCA1/2analysis in 311 women with DCIS and 392 with G1BC and extended panel testing (non-BRCA1/2) in 176/311 with DCIS and 156/392 with G1BC. We investigated PV detection by age at diagnosis, Manchester Score (MS), DCIS grade and receptor status.Results30/311 (9.6%) with DCIS and 16/392 with G1BC (4.1%) had aBRCA1/2PV (p=0.003), and 24/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Studies of germline BRCA1/2 pathogenic variants and contralateral breast cancer risk. The systematic review of the literature identified 15 articles (13 studies [37][38][39][40][41][42][43][44][45][46][47][48][49] and two meta-analyses 50,51 ) that inform the question of whether all patients with local recurrence or contralateral primary breast cancer should be offered BRCA1/2 testing. With the exception of one study that provides direct evidence, 38 the studies identified constitute indirect evidence in support of the recommendation that BRCA1/2 testing should be offered to patients with contralateral breast cancer or ipsilateral second breast primary.…”
Section: Literature Review and Analysismentioning
confidence: 99%
“…Studies of germline BRCA1/2 pathogenic variants and contralateral breast cancer risk. The systematic review of the literature identified 15 articles (13 studies [37][38][39][40][41][42][43][44][45][46][47][48][49] and two meta-analyses 50,51 ) that inform the question of whether all patients with local recurrence or contralateral primary breast cancer should be offered BRCA1/2 testing. With the exception of one study that provides direct evidence, 38 the studies identified constitute indirect evidence in support of the recommendation that BRCA1/2 testing should be offered to patients with contralateral breast cancer or ipsilateral second breast primary.…”
Section: Literature Review and Analysismentioning
confidence: 99%
“…A total of nine studies (22)(23)(24)(25)(26)(27)(28)(29)(30) presented frequencies of germline variants that allowed the following comparisons: HR-HER2+ versus TNBC (Supplementary Figure 5), HR-HER2+ versus HR+HER2-(Supplementary Figure 6), HR+HER2+ versus TNBC (Supplementary Figure 7), HR+HER2+ versus HR+HER2-(Supplementary Figure 8), and HR+HER2+ versus HR-HER2+ (Supplementary Figure 9). Moreover, eleven studies (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) allowed the comparison of HR+HER2versus TNBC (Supplementary Figure 10). For each comparison, genes were included when a variant was reported in at least two studies.…”
Section: Meta-analysis Of Germline Variants Among Bc Subtypesmentioning
confidence: 99%